The need for teaching undergraduate students the pesticides label contents In Faculties of Agriculture - Marcela Pimid; Kumara Thevan Krishnan (Universiti Malaysia Kelantan, 2015)
Pesticides labels contain specific information that is of interest at various pesticide handling stages. In current study, 14 students from Faculty of Agro Based Industry, University Malaysia Kelantan, Malaysia were assessed on their ability to understand the content of 14 pesticides product labels. The results of this study indicate that students were able to retrieve information such as hazard class, manufacturer and signal word with accuracy of 97.5 %, 98.7 % and 86.2 % without any formal training, respectively. Meanwhile, the worst performances of students were in retrieving information of the type of formulation from the pesticide product label which, only 4 responses (5 %) were accurate.